SINGLE-LAYER ORGANIC SEMICONDUCTOR SOLAR CELLS - Cvikl Bruno (Journal of Energy Technology, 2024)
The physical processes occurring within a singleͲlayer organic semiconductor solar cell under steadyͲstate illumination leading to a short circuit current for the zero externally applied bias voltage are investigated. In the unipolar, singleͲlayer metal/organic/metal structure, on account of the exponential decrease of light intensity within the organic material, the concentration of excitons is a function of the position within it. The charge recombination becomes spatially nonͲ uniform, leading to the spatial dependent trap density. The short circuit current represents the uncompensated (by the builtͲin electric field separated) charges, which are, on the average, at most one exciton diffusion length away from the electrode. The model is applied to the holeͲ only singleͲlayer poly(paraͲphenilene thienylene) organic solar cell ITO/LPPPT(59 nm)/Al published currentͲvoltage data for which the spatial dependence of the internal potential, the resulting internal electric field, and the trap charge density is calculated.